PENGARUH GOOD CORPORATE GOVERNANCE, KUALITAS LABA DAN UKURAN PERUSAHAAN PADA KINERJA PERUSAHAAN - Theacini, Deby Anastasia Meilic; Wisadha, I Gde Suparta (E-Jurnal Akuntansi; Vol 7 No 3 (2014), 2014)
Realize a good performance is the goal of every company, but the fact so many large companies suffered losses and failed to show healthy performance or the performance, especially after the crisis that occurred in 2008. This study aimed to determine and test empirically the effect of good corporate governance, earnings quality, and firm size on the performance of manufacturing firms went public 2009-2011. A total of 36 samples selected by purposive sampling method and multiple linear regression analysis as a technique of data analysis. The analysis finds that the size of the board of directors, managerial ownership, institutional ownership, quality of earnings, and firm size have a significant effect on the performance of the company partially, while the number of audit committee and the proportion of independent directors has no significant effect .
Keywords: GCG, earnings quality, firm size